Relationship Between Motivation, and Commitment With Performance At PT. Airindo Mustika Express (Survey in Head Office) - Sri Handoko Sakti (JURNAL LENTERA BISNIS, 2015)
This study is aimed at investigating  the relationship between the motivation, and commitment, with performance at PT Airindo Mustika Express (in head office).           This survey was conducted with a sample of 35 selected randomly as sample group. Data was collected by standard questionnaire.The research concludes that there is positive correlation between : (1) the motivation and performance, (2) the commitment and performance, (3) Besides that, there is positive correlation between the motivation, and commitment with performance.         Therefore, based on the results of the study:  (1) There is a positive relationship between motivation and performance of employees, (2) there is a positive and significant relationship between commitment and employee performance, (3) and there is a positive and significant relationship between both motivation and commitment to  employee performance. Key words : motivation, commitment, performance